In Vivo Assessment of Local Phosphodiesterase Activity Using Tailored Cyclic Nucleotide–Gated Channels as Camp Sensors - Rich, Thomas C. (The Rockefeller University Press, 2001)
Phosphodiesterases (PDEs) catalyze the hydrolysis of the second messengers cAMP and cGMP. However, little is known about how PDE activity regulates cyclic nucleotide signals in vivo because, outside of specialized cells, there are few methods with the appropriate spatial and temporal resolution to measure cyclic nucleotide concentrations. We have previously demonstrated that adenovirus-expressed, olfactory cyclic nucleotide–gated channels provide real-time sensors for cAMP produced in subcellular compartments of restricted diffusion near the plasma membrane (Rich, T.C., K.A. Fagan, H. Nakata, J. Schaack, D.M.F. Cooper, and J.W. Karpen. 2000. J. Gen. Physiol. 116:147–161). To increase the utility of this method, we have modified the channel, increasing both its cAMP sensitivity and specificity, as well as removing regulation by Ca(2)+-calmodulin. We verified the increased sensitivity of these constructs in excised membrane patches, and in vivo by monitoring cAMP-induced Ca(2)+ influx through the channels in cell populations. The improved cAMP sensors were used to monitor changes in local cAMP concentration induced by adenylyl cyclase activators in the presence and absence of PDE inhibitors. This approach allowed us to identify localized PDE types in both nonexcitable HEK-293 and excitable GH4C1 cells. We have also developed a quantitative framework for estimating the K(I) of PDE inhibitors in vivo. The results indicate that PDE type IV regulates local cAMP levels in HEK-293 cells. In GH4C1 cells, inhibitors specific to PDE types I and IV increased local cAMP levels. The results suggest that in these cells PDE type IV has a high K (m) for cAMP, whereas PDE type I has a low K (m) for cAMP. Furthermore, in GH4C1 cells, basal adenylyl cyclase activity was readily observable after application of PDE type I inhibitors, indicating that there is a constant synthesis and hydrolysis of cAMP in subcellular compartments near the plasma membrane. Modulation of constitutively active adenylyl cyclase and PDE would allow for rapid control of cAMP-regulated processes such as cellular excitability.